Physiological And Haemato-Biochemical Profiling Of Domestic Geese (Anser Anser Domesticus) Of Kashmir (Applied Biological Research, 2014)
Area-specific profiling of physiological and biochemical parameters in different species is prerequisite for establishing reference values valid for  clinical practice. The present study was aimed at physiological, haemato logical and biochemical profiling of domestic geese of Kashmir. The study was conducted on 30 adult domestic geese comprising of 12 male and 18  female (procured locally) which were maintained at Centre of Research on  Poultry, SKUAST-Kashmir. The average body temperature, respiration  rate and heart rate in geese were 40.05 ± 0.15oC, 17.16 ± 0.75 breaths min-1 and 60.57±5.09 beats min-1, respectively. Electrocardiogram (ECG) showed  presence of P, QRS and T waves. The mean electrical axis/ instantaneous  mean vector ranged from -86 to -95oindicating its orientation along the  long axis of body and superior to frontal plane. The amplitude of QRS  wave was almost similar and highest in lead II and III, whereas lead I  could hardly represent voltages of QRS wave. The voltage in QRS wave  ranged from 0.9 to 1.3 mv. The mean hemoglobin, ESR, PCV, TEC, MCV,  MCH, MCHC and TLC was 11.5 ± 0.2 mg dL-1, 0.1 ± 0.17 mm hr-1, 50.08 ± 1.81%, 3.06 ± 0.78 x 106 mm3, 166.13 ± 5.35 m3, 38.25 ± 1.26 pg, 23.14 ± 0.50% and 67.01 ± 4.08 x 103 mm3, respectively. The differential leukocyte  count revealed overall mean of 89.27±1.36, 7.77±1.30, 2.95±0.45 and 0.0%  heterophils, lymphocytes, monocytes and basophils, respectively. The blood  glucose, total protein, cholesterol-LS and HDL-cholesterol levels were 216.3 ±5.5 g dL-1, 21.59± 1.29 g L-1, 123.0 ±10.4 mg dL-1and 29.04 ±2.24 mg dL-1,  respectively. Gender-wise, only heart rate and body temperature showed a  significant difference. The present study established basic physiological  and haemato-biochemical indices of Kashmir geese.
Keywords: Biochemistry; electrocardiogram; geese; haematology; Kashmir; physiology